Genetic studies on Quality Protein Maize (QPM) for variability and diversity analysis under temperate conditions (Zea mays L.) - Ajaz, A L; Zahoor, A D; Sapna, J; Vishva, D C; Shourabh, J; Dhamni, P; Amit, L; Aman, T; Valeeta, M D; Sagar; et al. (Plant Science Today, 2026)
Despite significant progress in maize improvement, information on the extent of genetic variability and trait relationships in Quality Protein Maize (QPM) germplasm under temperate conditions remains limited, constraining effective selection for yield and nutritional quality. The present investigation was conducted to assess genetic variability, heritability, character associations and genetic divergence among 50 QPM genotypes, including five checks. The experiment was laid out in an augmented block design (ABD) without replications at the Dryland Agriculture Research Station (DARS), Budgam and observations were recorded on 13 morphological and quality traits. A wide range of variability was observed for all traits. The phenotypic coefficient of variation (PCV) and genotypic coefficient of variation (GCV) were in a moderate range for most of the characters except for the number of days to maturity, shelling percentage and protein content. High heritability of characters like grain yield, kernels cob-1, number of cobs plant-1 and 100-seed weight, along with extensive genetic advance, suggests that additive gene effects are playing a predominant role and direct selection will be effective for improvement of these traits. After correlation analysis, it was observed that grain yield was robustly and positively allied with plant height, ear height, number of cobs plant-1, cob length, kernel rows cob-1, kernels cob-1 and 100-seed weight, whereas protein content showed negative association with yield. Genetic divergence assessed through Mahalanobis D² statistics classified the genotypes into eight clusters, with the highest inter-cluster distance observed between cluster IV and cluster VIII with 341.59, indicating scope for heterotic hybrid development. The mean grain yield was highest in cluster II, while superior protein content was observed in clusters III and cluster VIII. The current findings identified ten early-maturing genotypes with commendable yield and protein content, which can be effectively used in QPM breeding programs aimed at improving productivity and nutritional quality.